2007
DOI: 10.1093/pasj/59.sp3.s631
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Sunspot Oscillations in G Band and Ca II H Line with Solar Optical Telescope on Hinode

Abstract: Exploiting high-resolution observations made by the Solar Optical Telescope onboard Hinode, we investigate the spatial distribution of power spectral density of oscillatory signal in and around active region NOAA 10935. The G-band data show that in the umbra the oscillatory power is suppressed in all frequency ranges. On the other hand, in Ca II H intensity maps oscillations in the umbra, so-called umbral flashes, are clearly seen with the power peaking around 5.5 mHz. The Ca II H power distribution shows the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 24 publications
6
39
0
2
Order By: Relevance
“…Balthasar and Schleicher (2008) tried to detect oscillations observing an Fe i line formed in the lower to middle photosphere and did not find any evidence for penumbral waves. Bellot Rubio et al (2000) found that the amplitude of the velocity oscillations increases toward the umbra/penumbra boundary, in agreement with the results by Nagashima et al (2007) and Lites (1988).…”
Section: Photospheric Velocity and Intensity Oscillationssupporting
confidence: 76%
See 3 more Smart Citations
“…Balthasar and Schleicher (2008) tried to detect oscillations observing an Fe i line formed in the lower to middle photosphere and did not find any evidence for penumbral waves. Bellot Rubio et al (2000) found that the amplitude of the velocity oscillations increases toward the umbra/penumbra boundary, in agreement with the results by Nagashima et al (2007) and Lites (1988).…”
Section: Photospheric Velocity and Intensity Oscillationssupporting
confidence: 76%
“…Using Hinode G-band temporal series of almost five hours of duration and one minute cadence, Nagashima et al (2007) calculated the photospheric power distribution of the intensity fluctuations in the G-band in a region containing a sunspot. Figure 7 shows the power distribution from 0.5 mHz to 5.5 mHz, at intervals of 1 mHz, revealing several important results.…”
Section: Photospheric Oscillationsmentioning
confidence: 99%
See 2 more Smart Citations
“…(i) the power enhancement is observed at high frequencies, between 5.5 and 7.5 mHz for waves that are usually nontrapped in the non-magnetic quiet Sun; (ii) the acoustic power measured in halos is higher than in the nearby quite Sun by about 40-60% (Hindman & Brown 1998;Braun & Lindsey 1999;Donea et al 2000;Jain & Haber 2002;Nagashima et al 2007); (iii) the halos are observed at intermediate longitudinal magnetic fluxes B = 50−300 G, while the acoustic power is usually reduced at all frequencies at larger fluxes (Hindman & Brown 1998;Thomas & Stanchfield 2000;Jain & Haber 2002); (iv) the radius of the halo increases with height. In the photosphere the halos are located at the edges of active regions, while in the chromosphere they extend to a large portion of the nearby quiet Sun (Brown et al 1992;Braun et al 1992;Thomas & Stanchfield 2000); (v) the power increase in the halo is qualitatively similar in sunspots, pores and plages; (vi) significant reflection of the upcoming acoustic radiation at 5-6 mHz is detected in active regions, unlike the behavior of such high-frequency waves in the quiet Sun .…”
Section: Introductionmentioning
confidence: 99%